Examining the overlap of young people’s early contact with the police as a person of interest and victim or witness - Athanassiou, Ulrika (Journal of criminology, 2021)
There is known to be considerable overlap among the victims and perpetrators of crime. However, the extent of this overlap early in life among children and young adolescents is not clear. We examined the sociodemographic profiles of young people who had early contact with police regarding a criminal incident as a person of interest, victim and/or witness, as well as the patterns of multiple police contact types from birth to 13?years of age. Data were drawn from a longitudinal, population-based sample of 91,631 young people from New South Wales, Australia. Among the 10.6% (n?=?9677) of young people who had contact with police, 14.4% (n?=?1393) had contact as a person of interest and as a victim and/or witness on two or more separate occasions. The most common first contact type was as a victim/witness, but those children with a first contact as a person of interest were most likely to have at least one further contact. Young people with both types of police contact were younger at first police contact, were more likely to reside in a socioeconomically disadvantaged area, and to be recorded as having an Aboriginal and/or Torres Strait Islander background. Our findings demonstrate that, by 13?years of age, 1 in 10 young people had been in early contact with police and that a minority have contact with the police as both a person of interest and a victim/witness. These young people may represent a particularly disadvantaged group in the community who are likely to be at risk of future adversity, including repeated contact with the criminal justice system.